Evaluation der Entscheidungshilfe Prostatakrebs aus Patientensicht: Ergebnisse der ersten 3 Monate = Evaluation of the decision aid “Entscheidungshilfe Prostatakrebs” fromthe patients’ view : results from the first three months - Groeben, Cornelius von der; Ihrig, Andreas (Der Urologe, 2016)
BackgroundThe decision aid “Entscheidungshilfe Prostatakrebs” is available online free of charge since June 2016. It is designed to support patients with their treatment decision-making and to lighten the burden on their treating urologists. This study evaluates usage data from the first 3 months.Materials and methodsThe ICHOM standard set was applied to allow a personalised presentation and to collect relevant data for subsequent counselling. Additionally, personal preferences and psychological burden were assessed amongst others. We collected anonymous data. A multivariate model evaluated predictors for high user satisfaction.ResultsFrom June through August 2016 a total of 319 patients used the decision aid, showing a continuous monthly increase in the number of users. There were n = 219 (68.7%) complete questionnaires. Median age was 66.1 ± 8.0 years. The oncological risk was low in 30.3%, intermediate in 43.6% and high in 26.1%. A majority of 57.5% used the decision aid together with their partner, 35.1% alone and 5.5% with their children. In all, 54.8% were “very satisfied” and 32.0% were “satisfied” with the decision aid for a total satisfaction rate of about 87%. The only predictors of total satisfaction were the usage mode and reported distress level.ConclusionsAs shown by the continuously increasing number of users this decision aid is becoming well established in German urology. Patients’ overall ratings are very positive. The majority of patients use the decision aid with their partner. This represents a significant advantage of a multimedia approach compared to print media.